Correcção da anemia dos doentes insuficientes renais crónicos em hemodiálise com eritropoietina recombinante humana: experiência de 12 meses. - F T de Sousa; M M Prata; J V Barbas; J P dos Santos (Acta Médica Portuguesa, 1990)
In this study we analyse the effects of the administration of recombinant human erythropoietin (rHuEpo) during 12 months to correct the anaemia in a group of 17 patients (9 men and 8 women; mean age 52.7 +/- 13.7; range 23 to 68 years) with end-stage renal disease (ESRD) on chronic haemodialysis (HD) for a range of 14 to 126 months (mean 43.1 +/- 29.6). In the correction period the rHuEpo was started at 50 U/Kg i.v. 3 times a week, immediately after each HD. This dose was maintained during 4 weeks and then increased in 25 U/Kg steps until haemoglobin (Hb) levels of 12 g/dl or a maximum dose of 100 U/Kg were reached. During the long-term maintenance period the individual rHuEpo dose was adjusted to keep the Hb constant at the target level of 10-12 g/dl. Baseline blood tests were done before the beginning of the treatment and every months afterwards. The levels of Hb increased significantly in week 4 and at the end of the first 3 month only 4 patients had no answer to rHuEpo. These patients had baseline serum ferritin levels below 100 ng/ml and responded well when this defficiency was corrected with oral iron. When levels of 30-35 vol% haematocrit (Hct) were reached the dose of rHuEpo could be reduced (150 to 200 U/Kg/week). The serum ferritin levels decreased 51% from a mean baseline level of 247.8 +/- 196 to 121.1 +/- 154.9 ng/ml with the onset of the maintenance phase (p less than 0.05).